2021
DOI: 10.1017/wet.2021.39
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tiafenacil applied preplant alone or mixed with metribuzin for glyphosate-resistant horseweed control in soybean

Abstract: Tiafenacil is a recently developed protoporphyrinogen IX oxidase (PPO)-inhibiting herbicide from the pyrimidinedione chemical class that is proposed for use as a preplant (PP) burndown in soybean. Glyphosate-resistant (GR) horseweed is a troublesome weed often found in no-till systems that can dramatically reduce soybean yield; control in soybean has been variable. Five field experiments were conducted over 2019 and 2020 in commercial soybean fields with GR horseweed to determine the biologically-effective-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…At 2, 4, and 8 WAA, there was no soybean injury from the PP herbicides evaluated (data not shown). This is consistent with other studies conducted with glyphosate + tiafenacil or saflufenacil, another PPO-inhibitor herbicide applied PP in a mixture with other herbicides in soybean (Miller et al, 2012;Budd et al, 2016aBudd et al, , 2016bWesterveld et al, 2021).…”
Section: Mhr Horseweed Control Studysupporting
confidence: 90%
See 2 more Smart Citations
“…At 2, 4, and 8 WAA, there was no soybean injury from the PP herbicides evaluated (data not shown). This is consistent with other studies conducted with glyphosate + tiafenacil or saflufenacil, another PPO-inhibitor herbicide applied PP in a mixture with other herbicides in soybean (Miller et al, 2012;Budd et al, 2016aBudd et al, , 2016bWesterveld et al, 2021).…”
Section: Mhr Horseweed Control Studysupporting
confidence: 90%
“…pha -1 in soybean. Westerveld et al (2021) observed 55-66% GR horseweed control with glyphosate + tiafenacil (900 + 25 g a.i. per ha -1 ) applied PP, and 87-90% GR horseweed control with glyphosate + tiafenacil + metribuzin (900 + 25 + 400 g a.i.…”
Section: Mhr Horseweed Control Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Glyphosate plus metribuzin, pyraflufen-ethyl/2,4-D, 2,4-D ester, halauxifen-methyl, saflufenacil or dicamba reduced GR Canada fleabane density 78, 68, 82, 88, 90, and 85%, respectively; density was not reduced with glyphosate plus tiafenacil. Similar reductions in GR Canada fleabane density have been reported in previous research (Budd et al, 2016;Eubank et al, 2008;Soltani et al, 2020a;Westerveld et al, 2021c;Zimmer et al, 2018b). When bromoxynil was added to glyphosate plus metribuzin, tiafenacil or pyraflufen-ethyl/2,4-D GR Canada fleabane density was reduced 7, 22, and 20%, respectively; density was not reduced when bromoxynil was added to glyphosate plus 2,4-D ester, halauxifen-methyl, saflufenacil or dicamba.…”
Section: Glyphosate-resistant Canada Fleabane Density and Biomasssupporting
confidence: 82%
“…Adding tiafenacil to glyphosate + dicamba did not improve GRCF control at 2, 4, or 8 WAA, and there was no reduction in density or biomass relative to glyphosate + dicamba (Table 4). Recent research by Westerveld et al [39] reported similar results with no improvement in GRCF control when adding tiafenacil (25 g ai ha −1 ) to glyphosate (900 g ae ha −1 ) + metribuzin (400 g ai ha −1 ) at 2, 4 and 8 WAA. In their study, there was also no decrease in GRCF density or biomass relative to glyphosate (900 g ae ha −1 ) + metribuzin (400 g ai ha −1 ).…”
Section: Control Of Glyphosate-resistant Canada Fleabanementioning
confidence: 74%